Effectiveness of Constructivistic-Based Blended Learning Model Through Computer Numerical Control Courses - Muslim, Muslim; K, Abdul Hamid; Saragih, Abdul Hasan (Advances in Social Sciences Research Journal, 2021)
This study examines the minimal number of credits and practical infrastructure in the CNC (Computer Numerical Control) course in the Department of Mechanical Engineering, Universitas Negeri Medan (UNIMED) which is a separate obstacle for students in improving competence of CNC course. An alternative and a solution in the form of constructivist-based blended learning model used in learning CNC course. The lack of literature studies on the use of constructivist-based blended learning models used in learning CNC course, so research is still needed on this problem. The purpose of this study was to determine the effectiveness of the constructivist-based blended learning model used in the learning process of the CNC machining course. The data collection process was carried out by using learning outcome tests. This type of research is a quasi-experimental study with a total sample of 56 students of the Mechanical Engineering Education Study Program of UNIMED on the engineering expertise competency of CNC course. The results of the data analysis raised 2 (two) themes that were discussed, namely: (1) constructivist-based blended learning model had an effect on learning outcomes of CNC Course in the Department of Mechanical Engineering Education, Unimed; and (2) constructivist-based blended learning model. The study of the two themes led to the conclusion that the two themes were effectively used in improving student learning outcomes in the CNC course at the Department of Mechanical Engineering Education, Unimed.